The Chemical Fluctuation Theorem governing gene expression - Seong Jun Park (Nature Portfolio, 2018)
A unified framework to understand gene expression noise is still lacking. Here the authors derive a universal theorem relating the biological noise with dynamics of birth and death processes and present a model of transcription dynamics, allowing analytical prediction of the dependence of mRNA noise on mRNA lifetime variability.